2013
DOI: 10.2141/jpsa.0120112
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Linseed and Palm Oils is a Better Alternative than Single Oil for Broilers Exposed to High Environmental Temperature

Abstract: This study was conducted to investigate the effects of combination of linseed oil (rich in omega 3 polyunsaturated fatty acid, ω3 PUFA) and palm oil (rich in saturated fatty acid, SFAs) on the growth performance, meat quality, and fatty acid composition of birds under high environmental temperature. Experiment was conducted in summer (average high temperature 31℃). Birds in the positive temperature control group (PTC) and negative temperature control group (NTC) were fed with maize-soybean meal-maize gluten ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Hence, rapeseed oil containing diet, which has a higher ratio of UFA and SFA lead to better fat digestibility (Nobakht et al, 2012). Similar to our findings, Wang et al (2013) and Khatun et al (2016) concluded in their study that FCR was in increasing trend with the increased levels of sunflower oil replacing palm oil when included at 6 per cent in the broiler ration. Barzan et al (2017) in their study also reported that canola oil supplementation had best production index in the sixth week when compared to that other oil sources like corn oil, animal fat, sunflower oil at 4 per cent.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, rapeseed oil containing diet, which has a higher ratio of UFA and SFA lead to better fat digestibility (Nobakht et al, 2012). Similar to our findings, Wang et al (2013) and Khatun et al (2016) concluded in their study that FCR was in increasing trend with the increased levels of sunflower oil replacing palm oil when included at 6 per cent in the broiler ration. Barzan et al (2017) in their study also reported that canola oil supplementation had best production index in the sixth week when compared to that other oil sources like corn oil, animal fat, sunflower oil at 4 per cent.…”
Section: Feed Conversion Ratiosupporting
confidence: 92%
“…The replacement of palm oil by rapeseed oil in broiler diet has increased profit per kg live weight and it was more in G 3 (Rs.12.06) and G 4 (Rs.11.14) groups which were replaced by 50 per cent and 100 per cent rapeseed oil, respectively. Similar to our result, Wang et al (2013) reported that replacing palm oil by linseed oil significantly decreased (P< 0.01) the total cost of production better economic results were achieved. Similarly Kuldipkar et.…”
Section: Techno-economicssupporting
confidence: 91%
“…Different fatty acid (FA) compositions also affect the absorption and utilization of fats and other nutrients. The absorption of fats is lower when FAs are saturated (SFA) and have a long chain (Ward and Marquardt, 1983), and fat utilization is normally higher in diets containing blends of fats and/or combinations of SFAs and unsaturated FAs (UFA) (Ketels and De Groote, 1989;Wang et al, 2013). Lin and Chiang (2010) and Tancharoenrat and Ravindran (2014) reported a greater formation of insoluble soaps (especially with Ca) with SFA compared to UFA.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also found broilers fed MO1 had decreased concentration of C18:1n-9 and C18:3n-3, as well as increased content of C20:5n-3, C22:6n-3, n-6 PUFA, n-3 PUFA, and total PUFA in breast muscle. Similarly, Wang et al [ 31 ] found a combination of linseed and palm oils in chicken diets had enhanced n-3 PUFA content in meat of broilers. These results are likely due to high concentrations of α-linolenic acid (C18:3n-3) in MO can act as a precursor for long chain n-3 PUFA in broilers, such as C20:5n-3 and C22:6n-3, so there are lower content of C18:3n-3 and higher deposition of n-3 PUFA in breast muscle of broilers [ 7 , 32 ].…”
Section: Discussionmentioning
confidence: 98%
“…A balanced n-6/n-3 PUFA ratios in diets could also help to decrease fat deposition by inhibiting fat synthesis [ 33 ]. Our study has demonstrated the beneficial effect of MO on health fatty acid profile of breast muscle in broilers, which may have economic benefits [ 31 ].…”
Section: Discussionmentioning
confidence: 99%